2022
DOI: 10.1159/000526277
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Urinary and Dietary Sodium-To-Potassium Ratios with Albuminuria in Community-Dwelling Japanese Adults: A Cross-Sectional Study

Abstract: Introduction: The urinary sodium-to-potassium ratio is an indicator of dietary sodium intake and has been associated with reduced kidney function. However, less is known about its association with albuminuria, the other key component of chronic kidney disease, in the community-dwelling adult population. We examined the association of the spot urinary sodium-to-potassium ratio with albuminuria and compared spot urinary and dietary sodium-to-potassium ratios. Methods: We quantified the association of the urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…There is no study investigating the relationship between the two from NHANES. Kabasawa et al ( 14 ) discovered a potential inverse link between potassium intake and albuminuria in another investigation. The research results of Burnier et al ( 35 ) and Elfassy et al ( 36 ) are opposite, and our research results are consistent with Burnier et al, increasing potassium intake may reduce the incidence of albuminuria.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There is no study investigating the relationship between the two from NHANES. Kabasawa et al ( 14 ) discovered a potential inverse link between potassium intake and albuminuria in another investigation. The research results of Burnier et al ( 35 ) and Elfassy et al ( 36 ) are opposite, and our research results are consistent with Burnier et al, increasing potassium intake may reduce the incidence of albuminuria.…”
Section: Discussionmentioning
confidence: 97%
“…Effect of albuminuria on dietary potassium intake, Kabasawa et al found a positive correlation between dietary sodium-potassium ratio and albuminuria ( 14 ) but did not study the relationship between potassium and albuminuria. This study found that potassium may be a key factor affecting albuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations